Influence of antenatal physical exercise on heart rate variability and QT variability - Dareyoush Rassi (The Journal of Maternal-Fetal & Neonatal Medicine, 2017)
Objective: We sought to characterise the influence of an antenatal exercise programme on ECG-derived cardiac variables. Methods: Fifity-one healthy pregnant women were recruited and randomly assigned (2 × 2×2 design) to an exercise group or a control group. Exercising groups attended weekly classes from the 20th week of pregnancy onwards. Cardiovascular assessments (heart rate variabiliy (HRV), QT, and the QT variability index (QTVI)) were performed at 12–16, 26–28, 34–36 weeks and 12 weeks following birth, during supine rest and exercise conditions. Results: Advancing gestation was associated with an increased maternal heart rate (p = 0.001), shorter QT interval (p = 0.003), diminished HRV (p = 0.002) and increased QTVI (p = 0.002). Each of these changes was reversed within 12 weeks postpartum (p < 0.004). The Exercise group displayed exaggerated changes for all variables (except QT) but only during supine rest in the third trimester (p < 0.029). Conclusion: Advancing gestation is associated with a shift in HRV/QTVI towards values that have been associated with an elevated risk of arrhythmia. A 20-week exercise programme undertaken between mid and late pregnancy exaggerated these changes during rest in the third trimester of pregnancy.